Mozambique rising building a new tomorrow - Ross, Doris C. (International Monetary Fund, 2014)
This publication highlights Mozambique's remarkably strong growth over the two decades since the end of the civil war in 1992, as well as the major challenges that remain for the country to rise out of poverty and further its economic development. Chapters explore such topics as the role of megaprojects and their relationship to jobs and growth; infrastructure and public investment; Mozambique's quest for inclusive growth; developing the agricultural sector; and building a social protection floor.